Estudio para la determinación de un sitio Ramsar en la Provincia de Cotopaxí - Jácome Morales, Stalín Giovanny (2017)
Ecuador as a contracting member to the Ramsar Convention is committed to designating wetlands of international importance (Ramsar Sites). So far, the country has designated 18 Ramsar sites located throughout the national territory which is giving a total of 290,815 hectares where the 86% are protected areas, and 14% do not have a national protection category. This study in the Cotopaxi - Llanganates Ecological Biopassage has the purpose of extending the Ramsar Site of the Cotopaxi Province. The field work was carried out, the qualitative identification of flora and fauna, the lifting of local vectors, the verification of the Ramsar criteria and the filling of the information sheet of the Ramsar site. The ecological evaluations of Sayre et al. methodology. (2002) were used. It was identified the species of flora and fauna outstanding in the area as hay (Stipa ichu), chicory (Hypochaeris sessiliflora Kunth) and "almohadilla" (Xerophyllum humile), whitetail deer (Odocoileus virginianus ustus) and Condor (Vultur gryphus). It was determined that the Cotopaxi - Llanganates Ecological Biopassage has the characteristics necessary to be a Ramsar site according to the particularities set out in criteria one, two and three of the Ramsar Convention. KEY WORDS: Wetland, Conservation, Natural Resources, Environment, Flora, Fauna, Ramsar Convention